Pengaruh kompetensi pedagogik dalam meningkatkan hasil belajar IPS siswa di SMPN 1 Kasreman - Aisyah Dewi Syukuri; Agus Purnomo; Agung Wiradimadja (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
As an educator, a teacher must master competencies, one of which is pedagogical competence. Pedagogical competence is helpful in understanding students and managing learning, starting from planning, implementing, and evaluating learning. The importance of the pedagogical competence of social studies teachers in managing learning can improve students' social studies learning outcomes. The research objective is to analyze the effect of pedagogical competence on improving social studies learning outcomes of students at SMPN 1 Kasreman. The research method used a quantitative design with an experimental research type. Data analysis used simple linear regression. The determination of respondents used probability sampling techniques, namely stratified random sampling. The research instrument used online questionnaires through Google Forms. The results showed that Ha could be accepted, meaning that pedagogical competence positively and significantly improved social studies learning outcomes. This means that the higher the pedagogical competence, the higher the students’ learning outcomes. Based on the limited research on cognitive aspects of learning outcomes, the researcher recommends that future researchers investigate the effect of pedagogical competence on the affective and psychomotor aspects of student learning outcomes. Guru sebagai seorang pendidik harus menguasai kompetensi, salah satunya ialah kompetensi pedagogik. Kompetensi pedagogik berguna dalam memahami siswa dan mengelola pembelajaran mulai dari merencanakan, melaksanakan serta mengevaluasi pembelajaran. Pentingnya kompetensi pedagogik guru IPS dalam mengelola pembelajaran mampu meningkatkan hasil belajar IPS siswa. Tujuan penelitian yaitu untuk menganalisis pengaruh kompetensi pedagogik dalam meningkatkan hasil belajar IPS siswa di SMPN 1 Kasreman. Metode penelitian menggunakan desain kuantitatif dengan jenis penelitian eksperimen. Analisis data menggunakan regresi linier sederhana. Penentuan responden memakai teknik stratified random sampling. Instrumen penelitian yang dipakai adalah kuesioner online melalui google form. Hasil penelitian menunjukkan bahwa Ha dapat diterima, artinya kompetensi pedagogik guru berpengaruh positif dan signifikan dalam meningkatkan hasil belajar siswa. Maknanya semakin tinggi kompetensi pedagogik maka semakin tinggi pula hasil belajar siswa. Berdasarkan hasil penelitian yang terbatas pada hasil belajar aspek kognitif, maka peneliti merekomendasikan kepada peneliti selanjutnya untuk mengkaji pengaruh kompetensi pedagogik terhadap hasil belajar aspek afektif dan psikomotorik siswa.